Brain swelling and ischaemia in Kenyans with cerebral malaria. Issue 4 (April 1994) - Newton, C R; Peshu, N; Kendall, B; Kirkham, F J; Sowunmi, A; Waruiru, C; Mwangi, I; Murphy, S A; Marsh, K
Abstract : Computed tomography was performed on 14 unconscious Kenyan children recovering from cerebral malaria (seven of whom had another scan 12-120 days later) to elucidate the cause of intracranial hypertension and neurological sequelae. Brain swelling, defined as a loss of cerebrospinal fluid spaces, was documented in six children, while a further two had conspicuously small ventricles only. There was severe intracranial hypertension in the two children with definite brain swelling in whom intracranial pressure was monitored. There was no evidence of acute hydrocephalus or vasogenic oedema. Four children with brain swelling also had widespread low density areas suggestive of ischaemic damage. The patterns of damage were not uniform but were consistent with a critical reduction in cerebral perfusion pressure (which was documented in the two in whom this was monitored), hypoglycaemia, or status epilepticus. All four had serious neurological sequelae. These data suggest that brain injury in cerebral malaria may be due in part to secondary systemic and intracranial factors as well as to the direct effect of intravascular sequestration.